Subintimal angioplasty for lower limb arterial chronic total occlusions - Chang, ZhiHui (Cochrane Database Syst Rev, 2016)
BACKGROUND: In recent years subintimal angioplasty (SIA) has become an established percutaneous procedure for the treatment of symptomatic lower limb arterial chronic total occlusions. However, the clinical benefits of this practice remain unclear. The aim of the review was to determine the effectiveness of SIA on clinical outcomes. This is an update of a review first published in 2013. OBJECTIVES: To assess the effectiveness of SIA versus other treatment for people with lower limb arterial chronic total occlusions, determined by the effects on clinical improvement, technical success rate, patency rate, limb salvage rate, and morbidity rates. SEARCH METHODS: The Cochrane Vascular Information Specialist searched the Cochrane Vascular Specialised Register (last searched January 2016) and Cochrane Central Register of Controlled Trials (CENTRAL) (2015, Issue 12). We also searched clinical trials registries. SELECTION CRITERIA: We included data from randomized controlled trials comparing the effectiveness of SIA and any other management method in the treatment of lower limb arterial chronic total occlusions. The primary intervention of interest was SIA, with or without a stent, for the restoration of vessel patency in people with occlusions of a lower limb artery. We compared SIA against alternative modalities used to restore vessel patency, including conventional percutaneous transluminal angioplasty, surgical bypass, or any other treatments. We compared different SIA devices and techniques against each other. DATA COLLECTION AND ANALYSIS: Two review authors independently selected trials, assessed trials for eligibility and methodological quality, and extracted data. The third review author resolved disagreements. MAIN RESULTS: Two studies, involving a total of 147 participants with TransAtlantic Inter‐Society Consensus (TASC)‐II D femoropopliteal lesions, met our inclusion criteria and were included in the review. Both studies were small but otherwise of high methodological quality. However, the treatment techniques and control groups of the two studies differed, precluding the combining of study results and resulting in the evidence being less applicable. We therefore considered the quality of the evidence to be low. In one study, participants with TASC‐II D lesions were randomized to receive either SIA with stenting of the superficial femoral artery or remote endarterectomy (RE) with stenting of the superficial femoral artery. Three‐year follow‐up results showed a Rutherford classification improvement of 64% in the SIA group compared to 80% in the RE group (risk ratio (RR) 0.79, 95% confidence interval (CI) 0.61 to 1.03; 95 participants; P = 0.079). Postexercise ankle brachial index improvements (defined as an increased value of 0.2) were reported in 70% of participants in the SIA group compared to 82% in the RE group (RR 0.86, 95% CI 0.68 to 1.08; 95 participants; P = 0.18). The study reported the technical success rate was 93% for the SIA group and 96% for the RE group (RR 0.97, 95% CI 0.88 to 1.07; 95 participants; P = 0.91). Primary patency at 12 months was 59.1% in the SIA group compared to 78.4% in the RE group (RR 0.75, 95% CI 0.57 to 1.00; 95 participants; P = 0.05). Primary patency at 24 months was 56.8% in the SIA group compared to 76.5% in the RE group (RR 0.74, 95% CI 0.55 to 1.00; 95 participants; P = 0.05) and 47.7% in the SIA group and 62.7% in the RE group at 36 months (RR 0.76, 95% CI 0.52 to 1.11; 95 participants; P = 0.15). Assisted primary patency was 52.3% in the SIA group compared to 70.6% in the RE group (P = 0.01) at 36 months. Secondary patency was better for the RE group (P = 0.03) at 36 months. Limb salvage at three years' follow‐up was 95% in the SIA group and 98% in the RE group (RR 0.97, 95% CI 0.90 to 1.05; 95 participants; P = 0.4). There were no perioperative deaths, but complications occurred in two SIA participants (femoral pseudoaneurysm and pulmonary edema) and in three RE participants (seroma, femoral pseudoaneurysm, superficial femoral artery acute occlusion). In the second study, the effects of the SIA OUTBACK re‐entry catheter device in people affected by TASC‐II D superficial femoral artery chronic total occlusion were compared with the SIA manual re‐entry technique. This study did not report clinical improvement and limb salvage. Technical success was achieved in all cases in both the OUTBACK device and manual groups. The primary 6‐month patency rate was 100% in the OUTBACK group (26 of 26 participants) compared to 96.2% in the manual group (25 of 26 participants) (RR 1.04, 95% CI 0.94 to 1.15). The primary 12‐month patency rate was 92.3% in the OUTBACK group (24 of 26 participants) compared to 84.6% in the manual group (22 of 26 participants) (RR 1.09, 95% CI 0.90 to 1.33). Patency rates at 24 and 36 months were not reported. The study reported that there were no complications. AUTHORS' CONCLUSIONS: Using the GRADE approach, we classified the quality of the evidence presented by both studies in this review as low due to small study size and the small number of studies. In addition, the two included trials differed from each other in the techniques and control used, and we were therefore unable to combine the data. Consequently there is currently insufficient evidence to support SIA over other techniques. Evidence from more randomized controlled trials is needed to assess the role of SIA in people with chronic lower limb arterial total occlusions.